2020
DOI: 10.1038/s41388-020-1207-6
|View full text |Cite
|
Sign up to set email alerts
|

PTGES/PGE2 signaling links immunosuppression and lung metastasis in Gprc5a-knockout mouse model

Abstract: Chronic inflammation has been linked to promotion of tumorigenesis and metastasis in lung. However, due to lack of a relevant animal model for characterization, the underlying mechanism remains elusive. Lung tumor suppressor gene Gprc5a-knockout (ko) mice are susceptible to lung inflammation, tumorigenesis and metastasis, which resembles the pathological features in human patients. Here, we showed that PTGES/PGE 2 signaling was highly associated with lung tumorigenesis and metastasis in Gprc5a-ko mice. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 48 publications
1
42
0
1
Order By: Relevance
“…Simultaneously, clinical, and epidemiological data have indicated that prolonged COX‐PGE 2 inhibition with NSAIDs at high dosages is associated with an increased risk of gastrointestinal and cardiovascular events compared with non‐NSAIDs (Mukherjee et al , 2001; Wang & Dubois, 2006; Sostres et al , 2010). Recently, Deng et al reported that a prostaglandin E Synthase inhibitor (Cay10526) suppressed tumor malignant progression in a spontaneous lung adenocarcinoma model (Wang et al , 2020); however, its clinical benefits require further investigation. To date, several EP4 antagonists have entered human clinical trials for the treatment of migraine, inflammatory diseases, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, clinical, and epidemiological data have indicated that prolonged COX‐PGE 2 inhibition with NSAIDs at high dosages is associated with an increased risk of gastrointestinal and cardiovascular events compared with non‐NSAIDs (Mukherjee et al , 2001; Wang & Dubois, 2006; Sostres et al , 2010). Recently, Deng et al reported that a prostaglandin E Synthase inhibitor (Cay10526) suppressed tumor malignant progression in a spontaneous lung adenocarcinoma model (Wang et al , 2020); however, its clinical benefits require further investigation. To date, several EP4 antagonists have entered human clinical trials for the treatment of migraine, inflammatory diseases, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin E 2 (PGE 2 ) is a key proinflammatory PG. PGE 2 upregulated TAMs and MDSCs contributed to immunosuppression and EMT-mediated lung metastasis to mouse lungs [53]. Apart from modulating EMT, PGE 2 derived from COX-2 induced expression of MIR675-5p, which inhibited p53 and promoted CRC metastasis [54].…”
Section: Eicosanoidsmentioning
confidence: 99%
“…MDSCs act to suppress the anti-tumoral activity of T cells and other cell types (Veglia et al, 2018). In a lung cancer model in which Gprc5a is deleted, increased PGE2 synthesis was also associated with recruitment of MDSCs as well as promotion of alternatively activated M2 macrophages (Wang et al, 2020). PGE2 has been shown to signal through the EP2 receptor to induce an immunosuppressive phenotype in MDSC (Porta et al, 2020).…”
Section: Role Of Prostaglandinsmentioning
confidence: 99%